2013
DOI: 10.1044/1058-0360(2012/12-0022)
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Speech Error Patterns Predict Articulation and Phonological Awareness Outcomes in Children With Histories of Speech Sound Disorders

Abstract: Purpose To determine if speech error patterns in preschoolers with speech sound disorders (SSDs) predict articulation and phonological awareness (PA) outcomes almost four years later. Method Twenty-five children with histories of preschool SSDs (and normal receptive language) were tested at an average age of 4;6 and followed up at 8;3. The frequency of occurrence of preschool distortion errors, typical substitution and syllable structure errors, and atypical substitution and syllable structure errors were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 46 publications
4
53
0
10
Order By: Relevance
“…This finding is consistent with the results from Raitano et al (14), Holm et al (22), and Peterson et al (15). Corresponding to other studies (12,16,31), this study has also shown that the children had more atypical error patterns in their speech have more problems with their PA skills.…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with the results from Raitano et al (14), Holm et al (22), and Peterson et al (15). Corresponding to other studies (12,16,31), this study has also shown that the children had more atypical error patterns in their speech have more problems with their PA skills.…”
Section: Discussionsupporting
confidence: 83%
“…A follow‐up at 12 years old (Leitao & Fletcher, 2004) showed that most of the sample continued to have literacy difficulties, and that the children with disordered speech at school entry were particularly impaired. These longitudinal findings were replicated in an independent sample of preschoolers with SSD: children who made disordered speech sound errors were more likely to have weak literacy skills at the age of 8 (Preston, Hull, & Edwards, 2013). …”
Section: Introductionmentioning
confidence: 81%
“…Leitao & Fletcher, 2004) and we found no strong evidence that disordered (rather than immature) speech errors are indicative of more serious deficits in phonological awareness and literacy (cf. Holm et al., 2008; Leitao & Fletcher, 2004; Leitão et al., 1997; Preston et al., 2013). The situation is different when SSD co‐occurs with language impairment as it frequently does: language impairment carries a strong risk of literacy difficulties affecting both word reading and reading comprehension skills.…”
Section: Discussionmentioning
confidence: 99%
“…In light of previous research (e.g. Preston et al, 2013;Rvachew et al, 2007), future research should also consider children's atypical speech errors when exploring links between polysyllable accuracy and literacy development. The data analysed using the WAP (Masso, 2016a) was only based on one single-word assessment task at one point in time.…”
Section: Future Researchmentioning
confidence: 99%
“…Children's productions of polysyllables are associated with phonological awareness and literacy abilities at school-age (Larrivee & Catts, 1999), and may assist with the identification of preschool children with speech sound disorders (SSD) who may be at risk of future literacy difficulties (Preston et al, 2013). Before further research into the association between polysyllable accuracy and literacy development can be conducted with preschool children with SSD, three issues need to be investigated: (1) task/s appropriate for sampling polysyllable productions of preschool children, (2) methods used to analyse and categorise error productions, and, (3) a framework to interpret the errors and polysyllable maturity of preschool children with SSD.…”
Section: Introductionmentioning
confidence: 99%